Effect of Competition on Unethical Behaviors - Abhijeet K. VADERA (Institutional Knowledge at Singapore Management University, 2014)
Competition can lead individuals to cheat; yet our knowledge of why competition affects unethical behaviors and how to mitigate these effects is still limited. Results of Study 1 show that competition facilitates unethical behaviors and that impaired moral awareness mediates these effects. Study 2 illustrates that moral elevation mitigates the effects of competition on cheating. Finally, Study 3 shows that moral identity moderates the curvilinear effects of competition on unethical behaviors such that only when competition is fierce, those with more salient moral identity are less likely to be dishonest than those with less salient moral identity.